Colectomy Averted: A Successful Case Report of Fidaxomicin Administration Through a Loop Ileostomy for Fulminant Clostridioides difficile Infection. Issue 2 (March 2020) - Brothers, Todd N.; Charpentier, Margaret M.; Shah, Shivani; Tandon, Richa
Abstract : Abstract: Clostridioides difficile infection is considered an urgent public health threat by the Centers for Disease Control and Prevention. Recent practice guidelines recommend either vancomycin or fidaxomicin for an initial episode of C. difficile infection and further recommend a subtotal colectomy in severe cases. There are limited data discussing novel approaches for fidaxomicin administration in severe C. difficile infection to avert colectomy. We describe an off-label route of fidaxomicin administration through a loop ileostomy twice daily with successful outcome. Abstract : Clostridioides difficile infection (CDI) is considered an urgent public health threat by the Centers for Disease Control and Prevention. Fulminant CDI has limited treatment options, and surgical intervention is typically warranted. This case describes a novel approach to the administration of fidaxomicin through a loop ileostomy in conjunction with standard treatment with great success, averting the need for colectomy.